2021
DOI: 10.1097/aog.0000000000004236
|View full text |Cite
|
Sign up to set email alerts
|

Prematurity Rates During the Coronavirus Disease 2019 (COVID-19) Pandemic Lockdown in Melbourne, Australia

Abstract: Low rates of preterm birth were observed during the coronavirus disease 2019 (COVID-19) lockdown in Melbourne, Australia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
87
3
3

Year Published

2021
2021
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(96 citation statements)
references
References 5 publications
3
87
3
3
Order By: Relevance
“…Of 9123 records in the initial search, 37 articles were eligible for inclusion, of which 36 were used in the quantitative synthesis 2,6‐10,15‐44 (Figure 1). Eighteen full‐text reports were excluded: reasons for the exclusions are provided in Appendix .…”
Section: Resultsmentioning
confidence: 99%
“…Of 9123 records in the initial search, 37 articles were eligible for inclusion, of which 36 were used in the quantitative synthesis 2,6‐10,15‐44 (Figure 1). Eighteen full‐text reports were excluded: reasons for the exclusions are provided in Appendix .…”
Section: Resultsmentioning
confidence: 99%
“…4 Results regarding preterm birth rates during COVID-19 lockdowns are conflicting. [5][6][7][8][9][10][11] A recent meta-analysis of 40 studies from January 1, 2020 to January 8, 2021 found a reduction in the overall preterm birth rate for high income countries (12 studies) as an effect of COVID-19 pandemic lockdowns. 12 This reduction appeared to be driven by a reduction in spontaneous preterm birth.…”
Section: Discussionmentioning
confidence: 99%
“…What has been studied to a great extent in the past year is the effect of Covid-19 lockdowns on preterm birth rates. Previous studies have found reductions in preterm birth rates during lockdown compared to prior to lockdown in Denmark, Ireland, US and Australia, [5][6][7][8] but studies from Spain, China and US have not found such associations. [9][10][11] A recent meta-analysis found a reduction in overall preterm birth for high income countries only.…”
Section: Introductionmentioning
confidence: 99%
“…Up to date, there are few reports that investigated the association between adverse birth outcomes and city lockdown during the COVID-19 pandemic period. Matheson et al recently reported low rates of preterm births during the COVID-19 lockdown in Melbourne, Australia (6). They observed lower rates of prematurity at <28, <34 and <37 weeks gestations with odds ratios of 0.46, 0.71 and 0.81, respectively, in the 2448 births during the pandemic city lockdown period of July-September 2020 when compared with the 2,514 births during July-September 2019 before pandemic.…”
Section: Discussionmentioning
confidence: 97%